In-Operando Quantification of Electrode Flooding in CO2 Electrolysis and Correlation to Product Distribution - Rottmann, Daniel M.; Kollmuss, Ricarda; Haufe, Stefan; Mayrhofer, Karl (Journal of The Electrochemical Society, 2025)
Flooding of the gas diffusion electrode (GDE) is one of the most important failure mechanisms limiting the long-term stability of CO2 electrolysis. Methods to characterize the GDE flooding process during the electrochemical reduction of CO2 are essential in order to improve the understanding of this failure mechanism and to consequently accomplish a steady performance at industrially relevant operation conditions. Here, a method for in-operando quantification of GDE flooding is presented. By collecting and weighing the amount of electrolyte which leaked through the GDE of a flow cell electrolyzer, utilizing a water trap on a balance, a time-resolved correlation between flooding data and product distribution is obtained. To demonstrate its potential, the in-operando weighting is used to determine leakage rates under dynamic and static CO2 electrolysis conditions and correlate them with the distribution of the gaseous reaction products. This new technique provides a deeper understanding of the dynamic processes behind GDE flooding during CO2 electrolysis and its influence on the product distribution, enabling the development of novel mitigation strategies.
CRIS-Team Scopus Importer:2025-05-30
Keywords: CO; electrocatalysis; failure mechanism; GDE flooding; in-operando